Enabling Enduring Evidence-Based Policy for the Southern Ocean Through Cultural Arts Practices - Roberts, Lisa; Kutay, Cat; Melbourne-Thomas, Jess; Petrou, Katherina; Benson, Tracey M.; Fiore, Danae; Fletcher, Paul; Johnson, Ellery; Silk, Melissa; Taberner, Stephen; Filgueira, Victor Vargas; Constable, Andrew J. (Frontiers in Ecology and Evolution, 2021)
This paper provides a perspective on how art and cross-cultural conversations can facilitate understanding of important scientific processes, outcomes and conclusions, using the Marine Ecosystem Assessment for the Southern Ocean (MEASO) as a case study. First, we reflect on our rationale and approach, describing the importance of deeper communication, such as through the arts, to the policy process; more enduring decisions are possible by engaging and obtaining perspectives through more than just a utilitarian lens. Second, we draw on the LivingData Website [http://www.livingdata.net.au] where art in all its forms is made to bridge differences in knowledge systems and their values, provide examples of how Indigenous knowledge and Western science can be complementary, and how Indigenous knowledge can show the difference between historical natural environmental phenomena and current unnatural phenomena, including how the Anthropocene is disrupting cultural connections with the environment that ultimately impact everyone. Lastly, we document the non-linear process of our experience and draw lessons from it that can guide deeper communication between disciples and cultures, to potentially benefit decision-making. Our perspective is derived as a collective from diverse backgrounds, histories, knowledge systems and values.